ESTIMATION OF THE DYNAMIC RANGE FOR ELECTROMAGNETIC FIELDS OF CELLULAR PHONES TAKING INTO ACCOUNT NEAR-FIELD ZONES OF THEIR ANTENNAS - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Results of the analysis of physical limits influence of the spherical wave model used for representation of an electromagnetic radiation of cellular phones on procedures adequacy of the probability estimation of its electromagnetic fields dynamic range near ground surface, are resulted. It is indicated, that taking into account these limitations practically does not affect on results of this estimation, but allows to simplify the procedure of a probability estimation of levels of predominating signals of cellular phones in places of its heavy use.